Changes in Melanin and Melanocytes in Mottled Hypopigmentation after Low-Fluence 1,064-nm Q-Switched Nd:YAG Laser Treatment for Melasma - Jang, Yong Hyun; Park, Ji-Youn; Park, Young Joon; Kang, Hee Young (Annals of dermatology, 2015)
KCI Citation Count: 9